Synthesis of Cosecant Linear Antenna Array Pattern using a Novel Modified Invasive Weeds Optimization - Kenane, El Hadi; Djahli, Farid; Bartil, Arres (Elektronika ir Elektrotechnika, 2015)
In this paper, a new modified method is presented for the synthesis of a linear antenna array to obtain a desired array pattern (shaped or pencil) with low side lobe level. Based on the original invasive weeds optimization (IWO), our modified IWO (MIWO) uses the process of mutation for the calculation of standard deviation. The shaped beam pattern is synthesized by respecting a desired cosecant pattern and supressing side lobe level to -25 dB. To achieve the desired pattern, both amplitude and phase of each element in the array are optimized when the spacing between the elements is fixed to the half wavelength. For the desired pencil beam pattern, the inter-element spacing’s are controlled while maintaining uniform excitations. Selected examples, for both shaped and pencil beam, are presented to show the effectiveness and flexibility of the proposed method. DOI: http://dx.doi.org/10.5755/j01.eee.21.5.13332